Multicultural Elephantine (The Biblical archaeology review, 2024)
Through October 27, 2024 National Museums in Berlin Berlin, Germany smb.museum Elephantine sits at the historical southern border of ancient Egypt, by the modern city of Aswan. This strategic location made it an important trade and military post. Rich archaeological deposits and textual sources reveal the long and layered history of this island in the […]